Construction of sinusoid-scale microvessels in perfusion culture of a decellularized liver. (1st September 2019) - Watanabe, Masafumi; Yano, Koki; Okawa, Koki; Yamashita, Tadahiro; Tajima, Kazuki; Sawada, Kazuaki; Yagi, Hiroshi; Kitagawa, Yuko; Tanishita, Kazuo; Sudo, Ryo
Graphical abstract: Abstract: There is a great deal of demand for the construction of transplantable liver grafts. Over the last decade, decellularization techniques have been developed to construct whole liver tissue grafts as potential biomaterials. However, the lack of intact vascular networks, especially sinusoids, in recellularized liver scaffolds leads to hemorrhage and thrombosis after transplantation, which is a major obstacle to the development of transplantable liver grafts. In the present study, we hypothesized that both mechanical (e.g., fluid shear stress) and chemical factors (e.g., fibronectin coating) can enhance the formation of hierarchical vascular networks including sinusoid-scale microvessels. We demonstrated that perfusion culture promoted formation of sinusoid-scale microvessels in recellularized liver scaffolds, which was not observed in static culture. In particular, perfusion culture at 4.7 ml/min promoted the formation of sinusoid-scale microvessels compared to perfusion culture at 2.4 and 9.4 ml/min. In addition, well-aligned endothelium was observed in perfusion culture, suggesting that endothelial cells sensed the flow-induced shear stress. Moreover, fibronectin coating of decellularized liver scaffolds enhanced the formation of sinusoid-scale microvessels in perfusion culture at 4.7 ml/min. This study represents a critical step in the development of functional recellularized liver scaffolds, which can be used not only for transplantation but also for drug screening and disease-modeling studies. Statement of Significance: Decellularized liver scaffolds are promising biomaterials that allow production of large-scale tissue-engineered liver grafts. However, it is difficult to maintain recellularized liver grafts after transplantation due to hemorrhage and thrombosis. To overcome this obstacle, construction of an intact vascular network including sinusoid-scale microvessels is essential. In the present study, we succeeded in constructing sinusoid-scale microvessels in decellularized liver scaffolds via a combination of perfusion culture and surface coating. We further confirmed that endothelial cells in decellularized liver scaffolds responded to flow-derived mechanical stress by aligning actin filaments. Our strategy to construct sinusoid-scale microvessels is critical for the development of intact vascular networks, and addresses the limitations of recellularized liver scaffolds after transplantation.